2018
DOI: 10.1037/dev0000616
|View full text |Cite
|
Sign up to set email alerts
|

Robust stability and physiological correlates of infants’ patterns of regulatory behavior in the still-face paradigm at 3 and 9 months.

Abstract: This study examined the stability of three patterns of infant regulatory behavior identified in the face-to-face still-face (FFSF) paradigm at 3 and 9 months-social-positive oriented, distressedinconsolable, and self-comfort oriented-and whether variations in infants' heart-rate were correlated with them. Although some studies have examined the stability of discrete infant behaviors, none have investigated the stability of early regulatory patterns across FFSF episodes over time. Healthy full-term infants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 36 publications
4
16
1
3
Order By: Relevance
“…The most common regulatory pattern observed for infants in the Brazilian sample was the Distressed-Inconsolable Oriented pattern (44.6%), followed by the Social-Positive Oriented (36.5%) and the Self-Comfort Oriented patterns (18.9%). In contrast, the distribution of regulatory patterns for infants in the Portuguese sample was consistent with those reported in other Portuguese samples [ 7 ]. The most common regulatory pattern for the Portuguese infants was the Social-Positive Oriented pattern (53.2%), followed by the Distressed-Inconsolable (35.5%) and the Self-Comfort Oriented patterns (13.3%).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The most common regulatory pattern observed for infants in the Brazilian sample was the Distressed-Inconsolable Oriented pattern (44.6%), followed by the Social-Positive Oriented (36.5%) and the Self-Comfort Oriented patterns (18.9%). In contrast, the distribution of regulatory patterns for infants in the Portuguese sample was consistent with those reported in other Portuguese samples [ 7 ]. The most common regulatory pattern for the Portuguese infants was the Social-Positive Oriented pattern (53.2%), followed by the Distressed-Inconsolable (35.5%) and the Self-Comfort Oriented patterns (13.3%).…”
Section: Resultssupporting
confidence: 87%
“…Follow-up studies suggest that these early-emerging regulatory behavior patterns are relatively stable from 3 to 9 months of age [ 7 ] and are associated with variations in maternal interactive behavior in other contexts [ 8 ], and infants’ attachment security at age one [ 10 , 11 ]. Despite the apparent relevance of these patterns for infants’ socioemotional development, very few studies have examined the distribution of these regulatory patterns outside US and European countries, or evaluated whether these patterns differ across countries or in different socio-demographic contexts.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the distribution of the three patterns of infant regulatory behavior (Social-Positive Oriented, Distressed-Inconsolable, Self-Comfort Oriented) observed at 3 months in the FFSF is distinct to that reported in other studies conducted with infants at the same age. While in US and European studies (e.g., [6,8,10,24]) the Social-Positive Oriented pattern is the most prevalent pattern (ranging from 52% to 57%), in this sample it is the Distressed-Inconsolable. The Social-Positive Oriented pattern, an indicator of the infant ability to soothe his/her emotions in the context of reciprocal and positive interactions, was exhibited only by 32.5% of the sample while in most studies it is above 50%.…”
Section: Discussioncontrasting
confidence: 55%
“…US and European studies reported, in samples with low risk, that the Positive Others Oriented pattern is the most prevalent (e.g., [6,8,9]). In Portuguese studies with full-term infants, the Social-Positive Oriented pattern is the most prevalent (around 54% of the cases), followed by the Distressed-Inconsolable (around 35% of the cases) and by the Self-Comfort Oriented (around 11% of the cases) [10,11]. These patterns are relatively stable from 3 to 9 months of age [10] and are associated with infant-mother attachment [12,13], indicating their relevance for infant's socioemotional development.…”
Section: Introductionmentioning
confidence: 95%
“…More than half (55.1%) of the cases were classified as Social‐Positive Oriented, 10.2% as Distressed‐Inconsolable, and 34.7% as Self‐Comfort Oriented. Recently, using this coding system in a sample of healthy full‐term infants, Barbosa, Beeghly, Moreira, Tronick, & Fuertes () found a robust stability of these three patterns of regulatory behavior in the FFSF at 3 and 9 months. Overall, 84% of the 112 infants received the same classification at 3 and 9 months.…”
Section: Patterns Of Regulatory Behavior In the Ffsfmentioning
confidence: 99%